2022
DOI: 10.1029/2022gl098064
|View full text |Cite
|
Sign up to set email alerts
|

Climate Impacts and Potential Drivers of the Unprecedented Antarctic Ozone Holes of 2020 and 2021

Abstract: The radiative effects of polar ozone depletion act to cool and strengthen the stratospheric polar vortex (Randel & Wu, 1999;Waugh et al., 1999), and dynamical coupling between the stratosphere and troposphere acts to connect the changes in the stratospheric flow to the surface (Baldwin & Dunkerton, 2001;Thompson et al., 2005). At the surface, the changes in the flow associated with the ozone hole project onto the southern annular mode (Shindell & Schmidt, 2004;Thompson & Solomon, 2002). Thus the ozone hole has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…While the model indicates that the organic particles expanded the size of the September/October 2020 ozone hole by about 2.5 million km 2 , it does not explain its record longevity 38 , raising the question of the roles of natural variability and possible forcings (e.g., relation to the unusual mid-latitude ozone losses as well as the radiative effects of the particles themselves and resulting impacts on temperatures, winds, and stratosphere/troposphere coupling 38,40 ). Further work is needed to examine potential radiative and dynamical feedbacks of the aerosol and ozone changes.…”
Section: Discussionmentioning
confidence: 91%
“…While the model indicates that the organic particles expanded the size of the September/October 2020 ozone hole by about 2.5 million km 2 , it does not explain its record longevity 38 , raising the question of the roles of natural variability and possible forcings (e.g., relation to the unusual mid-latitude ozone losses as well as the radiative effects of the particles themselves and resulting impacts on temperatures, winds, and stratosphere/troposphere coupling 38,40 ). Further work is needed to examine potential radiative and dynamical feedbacks of the aerosol and ozone changes.…”
Section: Discussionmentioning
confidence: 91%
“…Nevertheless, it appears likely that the combined effects of climate change and ozone depletion could have impacted both the timing and magnitude of these wildfires with considerable consequences for ecosystems in this region. In contrast to 2019, a strong and persistent Antarctic ozone hole occurred in 2020 and 2021 [ 54 , 74 76 ] and this led to record surface UV irradiances at several sites across East Antarctica during early summer. It has been suggested that the Australian wildfires that occurred during the previous summer contributed to this strong ozone loss [ 18 , 54 – 56 , 71 , 72 , 74 ].…”
Section: Effects Of Stratospheric Ozone Depletion On Climate and Extr...mentioning
confidence: 99%
“… Ozone effects Climate extremes and associated effects Plant responses Animal responses, including humans Antarctica and Southern Hemisphere (September 2019–February 2020) Anomalously small ozone hole Wildfires in Australia produced aerosols that caused ozone depletion and black carbon particles that accelerated snow melt [ 76 ] Widespread loss of plant biomass in Australia [ 97 ] Loss of human life and adverse health effects; loss of domestic animals and wildlife [ 98 101 ] Heatwaves in Antarctica [ 102 ] Additional snow melt that caused temporary greening of some previously moribund moss beds in East Antarctica [ 53 , 103 ] Vascular plants on the Antarctic Peninsula appear to be faring better than mosses under global warming and the grass Deschampsia antarctica appears to be quite tolerant of in-vitro high temperature shock treatments [ 104 ] Extreme summer marine heatwaves increased chlorophyll a (an indicator of the abundance of phytoplankton) in the Southern Ocean [ 105 ] Hotter and longer heatwaves increased the mortality and decreased post-heatwave growth rates in the Southern Ocean diatom Actinocyclus actinochilus relative to milder, shorter heatwaves [ 106 ] Functional thermal limits for the Antarctic sea urchin ( Sterechinus neumayeri ) were determined under simulated marine heatwaves. Key biological functions vary in their thermal sensitivity and in their responses to different rates of warming [ 107 ] Arctic (January – April 2020) Anomalously large ozone depletion [ 8 ] Heatwave in the Siberian Arctic; accelerated loss of sea ice [ 96 ] Permafrost warming and thaw lead to landscape changes (retrogressive thaw slumps) and increased greenhouse gas emissions [ 108 ] Negative impacts on organisms that depend on sea ice; positive impacts on animals that thrive in open oceans [ 95 , 109 , 1...…”
Section: Effects Of Stratospheric Ozone Depletion On Climate and Extr...mentioning
confidence: 99%
See 1 more Smart Citation
“…For the months of September, October, and November, the polar cap average TCO was higher by 29%, 28%, and 26%, respectively, compared to the mean of the 2008–2018 period [ 26 ]. In contrast, the Antarctic ozone holes in spring 2020 and 2021 were amongst the largest and longest-lived in the observational record [ 27 , 28 ]. These long-lasting ozone holes, extending to times when snow has melted, may have had impacts on Antarctic organisms [ 29 ].…”
Section: Current and Future Status Of Atmospheric Ozonementioning
confidence: 99%